Морфо-функциональные особенности эндотелия лимфатических капилляров тонкой кишки кролика - Чернышенко, Л.В. (Вестник зоологии, 1969)
On the basis of studying the lymphatic system of rabbit’s small intestine new data were obtained on the endothelium of lymphatic capillaries of this organ. The central milk sinuses of fibres, the peculiarities of which depend on form and structure of the fibres, are the roots of the small intestine lymphatic system. The milk sinuses are typical sinusoids with large endothelium cells of star-like form which have breaks in the border cell layer. The structure peculiarities of these cells condition the active phagocytic activity of the sinuses. Milk sinuses turn directly into lymphatic capillaries of the I and II order and perivascular lymphatic capillaries of mucous-undermucous layer, the cells of which are usually of star-like form, but their dimensions are less. The presence of long spindlelike cells with little sinuous borders and temperate argyrophility is characteristic to endothelium of lymphatic capillaries of serous membrane. Argyrophility of endothelium, becomes less to the lower divisions of the intenstine.